Tapping height and season affect frankincense yield and wound recovery of Boswellia papyrifera trees - Cherenet, E.; Abiyu, A.; Getnet, A.; Sisay, K.; Dejene, T. (Elsevier, 2020)
Boswellia papyrifera (Del.) Hochst is a threatened tropical dryland tree species. It is the source of frankincense, valued for its industrial, religious and traditional uses. This tree species is reported as under threat due to mortality from wound and inappropriate frankincense harvesting techniques. Two experiments were conducted simultaneously in the lowlands of North Western Gonder Zone, Ethiopia. The first experiment aimed to understand the effect of tapping height and tree size on wound recovery and frankincense yield and the second experiment dealt with understanding the effect of tapping schedule on survival and frankincense yield of different tree diameter sizes. Larger trees tapped at 1 m above the ground had the fastest wound recovery and highest frankincense yield. Higher tree survival was observed when tapping and resting schedule was alternated over years. However, mortality was higher when trees were tapped in consecutive years, without a resting year. The mean frankincense yield was 78 and 535 g/tree/year for small and large trees, respectively. Our result suggested that tree size, tapping height and resting time all have a significant effect on frankincense yield and wound recovery. Alternate year tapping of larger trees, with resting every three years, and avoiding tapping small trees are recommended for best wound recovery, survival, and to ensure sustainable production of frankincense.